2015
DOI: 10.1016/j.fishres.2015.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Does lure colour influence catch per unit effort, fish capture size and hooking injury in angled largemouth bass?

Abstract: a b s t r a c tThe contemporary tackle box for recreational angling is packed with lures that cover the full spectrum of colours with the assumption that colour influences fishing success. Yet, there is little research that identifies how lure colour might influence capture rates or size-selectivity. Moreover, while much is known about the factors that influence hooking injury or hooking depth (which is a good predictor of mortality in released fish), to our knowledge no studies have examined if such factors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 23 publications
1
18
1
2
Order By: Relevance
“…What remains unanswered from this study is which specific cues fish used to avoid the spinnerbait compared with the plastic worms. While catch rates did not change between worm colours, it remains possible that the red and gold coloration of the spinnerbait may have in, and of, itself elicited more strikes, as has been shown for mackerel, Scomber japonicas Houttuyn (Hsieh, Huang, Wu, & Chen, ) ; however, for largemouth bass the role of colour in the attractiveness of a lure has been found to be muted (Moraga, Wilson, & Cooke, ). In addition to colour, the spinnerbait and plastic worms differed in several other aspects (texture, vibration given off during retrieve, speed of retrieval), which all could have influenced the vulnerability of fish (Lennox et al, ).…”
Section: Discussionmentioning
confidence: 95%
“…What remains unanswered from this study is which specific cues fish used to avoid the spinnerbait compared with the plastic worms. While catch rates did not change between worm colours, it remains possible that the red and gold coloration of the spinnerbait may have in, and of, itself elicited more strikes, as has been shown for mackerel, Scomber japonicas Houttuyn (Hsieh, Huang, Wu, & Chen, ) ; however, for largemouth bass the role of colour in the attractiveness of a lure has been found to be muted (Moraga, Wilson, & Cooke, ). In addition to colour, the spinnerbait and plastic worms differed in several other aspects (texture, vibration given off during retrieve, speed of retrieval), which all could have influenced the vulnerability of fish (Lennox et al, ).…”
Section: Discussionmentioning
confidence: 95%
“…For example, many specialized recreational anglers believe that soft plastic baits are more effective than spoons or crankbaits, and some scientific work corroborates this (Danner, Chacko, & Brautigam, ; Arlinghaus, Alós, et al, ). Some authors have suggested that the colour of the artificial lure can move fish to the vulnerable state (see Sensory ecology, Foraging ecology sections; Hsieh et al., ; Moraga, Wilson, & Cooke, ). Colour is surely context‐dependent, for instance, surface lures are simply silhouettes on sunny days (this extends to many other contexts as well).…”
Section: Review Of Factors Underlying Fish Vulnerabilitymentioning
confidence: 99%
“…; Moraga et al. ). Future work should explore the relationship between perceived angler targets (e.g., trophy fish), individual fishing techniques, and actual angler catches (e.g., catch per unit effort and fish sizes) to address the question of whether some fishing techniques have intrinsically higher catch rates of large‐ versus small‐sized fish?…”
Section: Discussionmentioning
confidence: 96%
“…; Moraga et al. ), and in the context of bass, bed‐fishing may represent a technique that capitalizes on the confinement of larger adults to shallow waters during the spawning season (Warren ; Dutterer et al. ).…”
Section: Discussionmentioning
confidence: 99%